The Canons of Nepali Writing in English - Pun, Min (Tribhuvan University Journal, 2017)
After Laxmi Prasad Devkota pioneered Nepali writing in English in the 1950s, Mani Dixit, Tek Bahadur Karki, Abhi Subedi, Padma Prasad Devkota, D.B. Gurung, Laxmi Devi Rajbhandari and a few others continued to write in English during the 1960s, 70s and 80s. But Nepali writing in English gained its momentum with the publication of Samrat Upadhyay's Arresting God in Kathmandu in 2000 and Manjushree Thapa's The Tutor of History in 2001. They were followed by a group of other aspiring Nepali writers who emerged with their works in English that took over the global readership. Therefore, this paper argues that Nepali writing in English has achieved its canonical status with Laxmi Prasad Devkota, Samrat Upadhyay and Manjushree Thapa as canons of Nepali writing in English.